A highly porous fiber electrode derived from Juncus effusus and its shape recovery and electrochemical capacitive properties. (September 2020) - Xia, T.; Wu, W.; Zhao, J.; Li, Q.; Ao, C.; Zhang, J.; Wang, Q.; Zhang, W.; Lu, C.
Abstract: Portable and wearable electronic devices have gained increasing popularity in recent years. However, they usually suffer from all kinds of local stress under mechanical deformation, which is inevitable and even causes permanent mechanical deformation over time. Herein, we report a novel shape recovery electrode material derived from the naturally occurring Juncus effusus (JE). Remarkably, the fiber-shaped JE exhibits unique three-dimensional (3D) reticular and hollow tubular microstructures. In order to provide JE with energy storage capability, the active materials, namely carbon nanotubes (CNTs) and polyaniline (PANI), were successively deposited on JE. The as-prepared JE-CNT-PANI was rather flexible and knittable and demonstrated attractive shape recovery properties in water and H2 SO4 solution. Even if serious deformation occurred, it would recover its original shape very rapidly once immersed in the solvent again. A symmetric supercapacitor (SC) assembled from JE-CNT-PANI fiber electrodes delivered a large specific capacitance of 117.00 F g −1 at a current density of 1 A g −1 (based on the mass of the entire electrode), which was comparable to or even outperformed many early reported two-electrode PANI-based SCs. In addition, the SC could have 112.4% of the original capacitance after 100 times of shape recovery, indicating its excellent electrochemical stability under deformation. These results strongly suggested that JE could potentially become a powerful resource for applications in electrochemical capacitive devices. Graphical abstract: Image 1 Highlights: JE has a unique three-dimensional reticular hollow tubular structure. JE-CNT-PANI electrode exhibits distinct solvent-induced shape recovery properties. The JE-CNT-PANI SC shows high electrochemical capacitive properties. The JE-CNT-PANI SC demonstrates excellent long-term cycling stability.